The role of the state government, civil society and programmes across sectors in stunting reduction in Chhattisgarh, India, 2006–2016 - Kohli, Neha; Nguyen, Phuong Hong; Avula, Rasmi; Menon, Purnima (BMJ, 2020)
Childhood stunting has declined in India between 2006 and 2016, but not uniformly across all states. Little is known about what helped some states accelerate progress while others did not. Insights on subnational drivers of progress are useful not just for India but for other decentralised policy contexts. Thus, we aimed to identify the factors that contributed to declines in childhood stunting (from 52.9% to 37.6%) between 2006 and 2016 in the state of Chhattisgarh, a subnational success story in stunting reduction in India.